2017
DOI: 10.15740/has/ijpp/10.1/92-95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungicides as seed tratment against coriander wilt disease caused by Fusarium oxysporum f.sp. corianderii

Abstract: Among all the tested fungicides, complete inhibition of the fungal growth i.e. 100.00 per cent was recorded with Bavistin (carbendazim) at 200 ppm and 500 ppm the tested concentrations. The next best fungicides in order of fungal growth inhibition were Carbendazim + Mancozeb (companion), Topsin-M (thiophanate methyl), Vitavax (carboxin + thiram) and Benomyl (benlate) which inhibited the fungal growth by Carbendazim was found significantly superior at 200 and 500 ppm with (100%) inhibition of mycelial growth fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Increasing the concentration of both tested fungicides showed more efficiency in reducing fungal growth. Such findings are consistent with those of Jat et al, (2017), who reported that the fungicides Topsin-M®, Rhizolex-T®, and Tecto® 500 SC had a significant suppression efficiency when used against F. oxysporum f.sp. corianderii invitro.…”
Section: Discussionsupporting
confidence: 92%
“…Increasing the concentration of both tested fungicides showed more efficiency in reducing fungal growth. Such findings are consistent with those of Jat et al, (2017), who reported that the fungicides Topsin-M®, Rhizolex-T®, and Tecto® 500 SC had a significant suppression efficiency when used against F. oxysporum f.sp. corianderii invitro.…”
Section: Discussionsupporting
confidence: 92%
“…(2001) [7] against Fusarium oxysporum f. sp. ciceri and Jat et al (2017) [4] against Fusarium oxysporum f. sp. corianderi.…”
Section: In Vitro Evaluation Of Fungal Biocontrol Agents Against Test Pathogenmentioning
confidence: 95%